Trade agreements - Carsten Kowalczyk; Raymond Riezman (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper reviews the most significant recent developments in the theory of trade agreements. The paper offers an integrated approach to evaluating trade agreements, and uses the approach to present results on preferential and multilateral trade agreements. The paper identifies also several questions for further research.
Keywords: F00; F02; F10; F11; F13; F15; 330; trade agreements; multilateralism; free trade; customs unions; free trade areas; preferential trade; Handelsabkommen; Wohlfahrtseffekt; Außenwirtschaftstheorie; Allgemeines Gleichgewicht; Freihandelszone; Zollunion; Außenhandelspräferenz; Theorie